2003
DOI: 10.1007/s00262-003-0388-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the CD4+/CD8+ ratio of tumour infiltrating lymphocytes in colorectal cancer and HLA-DR expression on tumour cells

Abstract: The purpose of this study was to clarify whether HLA-DR expression of colorectal tumour cells or the CD4+/CD8+ ratio of the tumour infiltrating lymphocytes is significantly associated with the prognosis of colorectal cancer. Using flow cytometry, we studied the tumour cell expression of the HLA class II in 70 enzymatically dissociated colorectal cancers and the phenotype of tumour infiltrating lymphocytes (TILs) in 41 cases. There was no trend in 5-year survival between three levels (low, medium, high) of HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
131
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(148 citation statements)
references
References 20 publications
12
131
0
5
Order By: Relevance
“…A lower ratio represents a higher number of cytotoxic CD8 C T cells in relation to helper CD4 C T cells and has been correlated with a good prognosis in colorectal cancer. 22 Consistent with the hypothesis that IL-21 promotes a Th1 bias and favors antitumor immunity, in this model, the CD4 C /CD8 C T cell ratio was more than two times higher in the IL-21KO-APC MIN/C mice intestines as compared with that of APC MIN/C mice (Figs. 3B and C).…”
Section: Il-21ko-apc Min/c Mouse Intestine Has Fewer Infiltrating T Csupporting
confidence: 87%
“…A lower ratio represents a higher number of cytotoxic CD8 C T cells in relation to helper CD4 C T cells and has been correlated with a good prognosis in colorectal cancer. 22 Consistent with the hypothesis that IL-21 promotes a Th1 bias and favors antitumor immunity, in this model, the CD4 C /CD8 C T cell ratio was more than two times higher in the IL-21KO-APC MIN/C mice intestines as compared with that of APC MIN/C mice (Figs. 3B and C).…”
Section: Il-21ko-apc Min/c Mouse Intestine Has Fewer Infiltrating T Csupporting
confidence: 87%
“…They found, by RT-PCR on 75 cases that mRNA levels of CD8, granzyme B and granulysin were significantly greater in patients without vascular emboli, lymphatic and perineural invasion (collectively known as VELIPI) compared to those with these features and that CD45RO+ cells had independent prognostic value [15] . Diederichsen et al [74] showed that a low CD4/CD8 ratio by flow cytometry was an independent prognostic factor for prolonged survival. In addition, Milasiene et al [75] evaluated inter-epithelial CD3, CD4, CD8, CD20 and CD16 and found that increased levels of all these markers, particularly of the natural killer cell marker CD16 led to significantly improved overall outcome [11,75] .…”
Section: T-lymphocytesmentioning
confidence: 99%
“…Several studies have shown that higher numbers of T-regulatory (T reg ) cells are associated with progression in a variety of malignancies, and T reg numbers appear increased in individuals with a variety of solid tumours (lung, breast and pancreas) and haematological malignancies, and this is reflected in the peripheral blood (PB) of cancer patients (Woo et al, 2001;Liyanage et al, 2002;Diederichsen et al, 2003;Javia and Rosenberg, 2003;Wolf et al, 2003;Marshall et al, 2004;Galon et al, 2006;Nedergaard et al, 2007). The T reg subgroup of immune cells suppresses the activity of effector cells, including CD4 þ and CD8 þ cytotoxic T cells, natural killer (NK) cells, dendritic cells, NK T (NKT) cells and B cells (Murakami et al, 2002;Trzonkowski et al, 2004).…”
mentioning
confidence: 99%